MATERIALISME : PENYEBAB DAN KONSEKUENSI - Fransisca Mulyono (Bina Ekonomi, 2011)
Materialism defined as the importance a person places on possessions and their acquisition as a necessary or desirable form of conduct to reach desired end states, including happiness. It has certain negative  effects : increasing  risk for diminished  well-being (happiness) afterwards lead to negative  subjective well-being,  low level se/f- determination,  low level gratitude  and negative meaning  in life. This is a phenomenon have been around everywhere and everyone:  kids, teenagers even adults, emerging because of ever increasing the symbolic consumption, not utilitarian consumption.  Some researchs showed that there are some causes be responsible for materialism: dominant social paradigm, peer group pressure, and conspicuous consumption. Concerning its negative effects, socialization process about materialism must be done to everybody comprehensively.